2021
DOI: 10.3390/ma14216379
|View full text |Cite
|
Sign up to set email alerts
|

Muntingia calabura Leaves Mediated Green Synthesis of CuO Nanorods: Exploiting Phytochemicals for Unique Morphology

Abstract: In this study, phytochemical assisted nanoparticle synthesis was performed using Muntingia calabura leaf extracts to produce copper oxide nanoparticles (CuO NPs) with interesting morphology. Scanning electron microscope (SEM) and transmission electron microscope (TEM) analysis of the biosynthesized CuO NPs reveal formation of distinct, homogeneous, and uniform sized CuO nanorods structure with thickness and length of around 23 nm and 79 nm, respectively. Based on Fourier-transform infrared (FTIR) analysis, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 57 publications
5
7
0
Order By: Relevance
“…The presence of the peculiar peak at 2300–2350 cm −1 in sample S2 might be due to the contamination from phytochemicals on the synthesized CuO NPs surface calcinated at low calcination temperature. Nevertheless, a sharp and intense peak located at 504–536 cm −1 only appeared in synthesized CuO NPs at higher calcination temperatures, indicating the presence of copper-oxygen bond vibration as reported between 420–613 cm −1 in other studies [ 2 , 18 , 22 , 24 , 40 , 41 , 42 , 43 ]. The absorption peak of metal oxides and hydroxides NPs are commonly located at the fingerprint region (wavenumber below 1000 cm −1 ) due to interatomic vibrations [ 76 ].…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The presence of the peculiar peak at 2300–2350 cm −1 in sample S2 might be due to the contamination from phytochemicals on the synthesized CuO NPs surface calcinated at low calcination temperature. Nevertheless, a sharp and intense peak located at 504–536 cm −1 only appeared in synthesized CuO NPs at higher calcination temperatures, indicating the presence of copper-oxygen bond vibration as reported between 420–613 cm −1 in other studies [ 2 , 18 , 22 , 24 , 40 , 41 , 42 , 43 ]. The absorption peak of metal oxides and hydroxides NPs are commonly located at the fingerprint region (wavenumber below 1000 cm −1 ) due to interatomic vibrations [ 76 ].…”
Section: Resultssupporting
confidence: 70%
“…The presence of phytochemicals in plant extract generates the electrons and causes the reduction of copper salt and conversion into CuO NPs [ 3 ]. As a result, the SPR resulted from the electron resonant oscillating at the conduction band initiated by incident electromagnetic radiation [ 2 , 22 , 40 , 41 ] at specific wavelength [ 62 ]. Thus, the absorption peak at 344–522 nm from the current study indicates the formation of CuO NPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, the decrease in particle size, as well as the increase in band gap energy of the as-prepared nanoparticles, signified the size quantization effects [16]. When particle size reached the nanosized scale, the overlapping of adjacent energy levels minimized and, subsequently, the width of energy band widened [17,18]. that this could be due to the more viscous nature of the aloe vera extract, which adheres to the surface of the nanoparticles during synthesis.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…rough X-ray photoelectron spectroscopy and Raman spectroscopic analysis, the phase purity and chemical identity of the product have been confirmed. ese results indicated that a single-phase CuO has been formed without the presence of any other impurities [44].…”
Section: Discussionmentioning
confidence: 81%